3D Interrelationship between Osteocyte Network and Forming Mineral during Human Bone Remodeling. Issue 12 (8th May 2021) - Ayoubi, Mahdi; van Tol, Alexander F.; Weinkamer, Richard; Roschger, Paul; Brugger, Peter C.; Berzlanovich, Andrea; Bertinetti, Luca; Roschger, Andreas; Fratzl, Peter
Abstract: During bone remodeling, osteoblasts are known to deposit unmineralized collagenous tissue (osteoid), which mineralizes after some time lag. Some of the osteoblasts differentiate into osteocytes, forming a cell network within the lacunocanalicular network (LCN) of bone. To get more insight into the potential role of osteocytes in the mineralization process of osteoid, sites of bone formation are three‐dimensionally imaged in nine forming human osteons using focused ion beam‐scanning electron microscopy (FIB‐SEM). In agreement with previous observations, the mineral concentration is found to gradually increase from the central Haversian canal toward pre‐existing mineralized bone. Most interestingly, a similar feature is discovered on a length scale more than 100‐times smaller, whereby mineral concentration increases from the LCN, leaving around the canaliculi a zone virtually free of mineral, the size of which decreases with progressing mineralization. This suggests that the LCN controls mineral formation but not just by diffusion of mineralization precursors, which would lead to a continuous decrease of mineral concentration from the LCN. The observation is, however, compatible with the codiffusion and reaction of precursors and inhibitors from the LCN into the bone matrix. Abstract : During bone remodeling, newly formed bone next to the Haversian canal gradually mineralizes in a mineral gradient from (unmineralized) osteoid toward mineralized bone. The tissue is pervaded by the lacunocanalicular network (LCN) which houses osteocytes and their processes. 3D imaging with focused ion beam scanning electron microscopy suggests that the LCN controls mineralization, possibly by releasing mineralization precursors and inhibitors into the matrix.